Florida's Citrus Canker Eradication Program (CCEP): Annual Economic Impact on Florida's Fresh and Processed Grapefruit Industry - Thomas H. Spreen; Marisa L. Zansler; Ronald P. Muraro (EDIS)
In the analysis presented in this paper, the benefits of the CCEP are predicted through an analysis of the Florida citrus industry under the scenario that citrus canker has become endemic. The estimated net change in revenue in the fresh and processed markets and the additional costs of production were the measurements of the predicted benefits. This is EDIS document FE534, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published March 2005.